2019
DOI: 10.1016/j.chemosphere.2019.05.238
|View full text |Cite
|
Sign up to set email alerts
|

Risk evaluation of biochars produced from Cd-contaminated rice straw and optimization of its production for Cd removal

Abstract: Enlighten-Research publications by members of the University of Glasgow http://eprints.gla.ac.uk  41% of Cd in raw rice straw was exchangeable, posing great environmental risks  Pyrolyzing at 300 °C did not significantly alter Cd fractions remained in biochar  Exchangeable fraction of Cd dropped to 5.79% at 500 °C and to 2.12% at 700 °C  Increasing temperature decreased exchangeable Cd fraction immobilized on biochar  CRSB700 has the fastest and highest Cd removal, and most stable Cd immobilization *Highl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…One reason for why CEC played a more important role for these biochars is that sewage sludge biochars can be relatively rich in N (up to 2.8%) and S (up to 2.3%) (Paz-Ferreiro et al, 2018;Waqas et al, 2015). Additionally, Shen et al (2019) demonstrated that increasing temperature decreased exchangeable Cd fraction immobilized on biochar, which may be representative in sewage sludge biochar.…”
Section: Correlation Between Pyrolysis Temperature and CD Retentionmentioning
confidence: 98%
“…One reason for why CEC played a more important role for these biochars is that sewage sludge biochars can be relatively rich in N (up to 2.8%) and S (up to 2.3%) (Paz-Ferreiro et al, 2018;Waqas et al, 2015). Additionally, Shen et al (2019) demonstrated that increasing temperature decreased exchangeable Cd fraction immobilized on biochar, which may be representative in sewage sludge biochar.…”
Section: Correlation Between Pyrolysis Temperature and CD Retentionmentioning
confidence: 98%
“…For example, if the Cd content in the straw were 6.35 mg kg −1 (Babu & Nagabovanalli, 2017), the exposure of Cd could reach 63.5 μg kg −1 day −1 body weight for a 1000 kg cow at a straw ingestion rate of 10 kg day −1 (Hoffman et al, 2008; Van Bruwaene et al, 1983), which poses a risk of Cd contamination of beef and dairy food for human consumption. Crop straw can also be carbonized form biochar for a variety of applications, however, the content of Cd in the biochar may increase due to the loss of volatile biomass during carbonization (Shen et al, 2019). Although the fraction of exchangeable Cd can decrease with high carbonization temperatures (Shen et al, 2019), the long‐term risk of residual Cd in biochar still warrants further attention.…”
Section: Figurementioning
confidence: 99%
“…Crop straw can also be carbonized form biochar for a variety of applications, however, the content of Cd in the biochar may increase due to the loss of volatile biomass during carbonization (Shen et al, 2019). Although the fraction of exchangeable Cd can decrease with high carbonization temperatures (Shen et al, 2019), the long-term risk of residual Cd in biochar still warrants further attention. In some rural areas, crop straw is still an important bioenergy source for household cooking and heating.…”
mentioning
confidence: 99%
“…Due to its high mobility, Cd can be easily absorbed by plants and then accumulate in the 3 human body via the food chain, inhalation of contaminated dust, dermal contact, and consumption of crops grown in polluted soil (DalCorso et al, 2008;Guo et al, 2011;Hu et al, 2017a;Ronzan et al, 2018). Cd a carcinogen that can damage the functioning of some human organs (Sawut et al, 2018;Shen et al, 2019;Xiang et al, 2019). Hence, modelling Cd accumulation and forecasting its temporal trends in agricultural soil are essential.…”
Section: Introductionmentioning
confidence: 99%